Flame Characteristic Of Premix Combustion Of Jatropha Curcas Oil And Cotton Seed The Addition Of Various Magnetic Field Directions - Mochammad Khoirul Rosidin; Dony Perdana; Khoirul Anam As Syukri; Firnanda Sumanjaya Putra; Muhamad Hanifudin (Jurnal Polimesin, 2024)
This study investigates an effects of various magnetic fieldsdirection on flames characteristic of premix combustions. Research is important as a reserve a fossil fuel using environmental friendly vegetable oil.Jatrophacurcas oil is mixed with cotton seeds (50% blend) as fuel.Experimentare carried out on cylindrical type burner. Vegetable oils were loaded on boiler, then heated on LPG stoves, while air was obtained from the compressor. Grade N52 nickel neodymium magnets atintensitymagnetic fieldsof 1.1 T were used in this study. The combustion characteristics are identified from the flame image and the temperature signal at the burner tip. The flame image is recorded using a video camera at highspeed, 120 frames per second. This research found that the magnetic field of an attractive produces a brighter, wider, and more stable flame compared to a repulsive magnet and without. The magnetic field changes the orientation of the hydrocarbon from the para state to the ortho state, so that it tends to break down the fuel molecules resulting in more complete and faster combustion causing the flame temperature to increase, but the flame height decreases.